Impact of forefoot cushionong stiffness on blocks start performance in sprinting - Denis, Y.; Knoke, H.; Kanjuh, M.; Braun, L.; Hipper, M.; Anedda, B.; Helwig, J.; Willwacher, S. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study aimed to identify the impact of different forefoot cushioning properties in "advanced spiked footwear" on sprinting performance during the block start. Kinetic parameters were collected for twenty-three competitive sprinters during a block sprint start in two advanced spike conditions with only a difference in forefoot cushioning stiffness. An instrumented start block was used to measure the ground reaction forces applied in the front and rear leg. The stiffer shoe condition showed significantly better performance for most parameters, suggesting a softer midsole in forefoot cushioning is not related to better block start performance. This study has demonstrated that differences in midsole materials can alter sprinting block performance and should be considered when analysing advanced spikes features, especially across different shoe brands and their cushioning technologies.